2005
DOI: 10.1093/wbro/lki007
|View full text |Cite
|
Sign up to set email alerts
|

Housing Policy in Developing Countries: Conjectures and Refutations

Abstract: This article discusses housing policy in developing economies. It examines recent research findings in light of earlier arguments as to the benefits of more market-oriented approaches. It also looks at whether the recommendations of earlier work have been refuted or developed in subsequent analyses and policy measures. In particular, it reviews the empirical analysis of the effects of policy on housing supply, the richer understanding of the effects that land market regulations have on housing affordability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(41 citation statements)
references
References 62 publications
(33 reference statements)
0
41
0
Order By: Relevance
“…Cash and other liquid assets are the second most important forms of collateral used across all firm sizes (approximately 22% of banks rate this form of collateral as the most important), followed by bank and personal guarantees (10%-15% of banks)." Buckley and Kalarickal (2005) qualify the widespread support for the link between housing and enterprise loan provision. They cite evidence that the process of establishing systems of secure title is not unproblematic and that the cost can outweigh the economic gains.…”
Section: F Small Business Development: Collateral and Business Premisementioning
confidence: 88%
See 1 more Smart Citation
“…Cash and other liquid assets are the second most important forms of collateral used across all firm sizes (approximately 22% of banks rate this form of collateral as the most important), followed by bank and personal guarantees (10%-15% of banks)." Buckley and Kalarickal (2005) qualify the widespread support for the link between housing and enterprise loan provision. They cite evidence that the process of establishing systems of secure title is not unproblematic and that the cost can outweigh the economic gains.…”
Section: F Small Business Development: Collateral and Business Premisementioning
confidence: 88%
“…Furthermore, Moser (1998) notes that contribution of small business development to poverty reduction depends partly on the assets that complement home ownership such as skills, electricity, and water supply. Buckley and Kalarickal (2005) argue that these warnings are not intended to suggest that secure title is not important for accessing the full benefits of home ownership. Instead, they note that ownership itself may not be sufficient and that "a set of interlocking, complementary reforms is also necessary" (Buckley and Kalarickal 2005, p. 246).…”
Section: F Small Business Development: Collateral and Business Premisementioning
confidence: 99%
“…Literature focusing on developing countries is more difficult to find. Malpezzi (1999) has a review that covers developed, developing and countries with transitional economies, while Buckley and Kalarickal (2005) include the subject as part of a broader review of housing policies in developing countries.…”
Section: The Effect Of Land Use Regulation On Housing Pricementioning
confidence: 99%
“… Attracting private (and community) sector investment into social housing is one of the main recommendations made by this study. In the literature, it is shown that the involvement of the private sector in social housing provision in many countries is viewed as being significant (Buckley & Kalarickal 2005;Erguden 2001). Nevertheless, this is not the case in…”
Section: Question Three: Recommendationsmentioning
confidence: 99%
“…Some studies have shown that more poor people in developing countries are living in urban areas. Social housing has been used as the main approach to help those poor people to get access to housing and, through this, to reduce poverty (Buckley & Kalarickal 2005). Generally, although many policies have been formulated and various programs and projects have been implemented around the world to deliver social housing, most are still far from achieving their aims, especially in developing countries (Erguden 2001;Omar 2003).…”
Section: Introductionmentioning
confidence: 99%